Governing by consensuses: On the legal regulation of the European Union's development cooperation policy - Morten Broberg (Danish Institute for International Studies (DIIS), 2010)
In 2009 the European Union and its Member States jointly provided development assistance totaling 49 billion Euro, amounting to more than half of all the world's development assistance. About one fifth - or 12 billion Euro - was managed by the European Commission. The regulation of how these very considerable amounts are to be spent to a very large extent is made in the form of soft law measures (i.e. non-binding measures) rather than as hard law measures (i.e. binding measures). This is surprising, not least when one takes the importance and the size of the amounts into account. In a recent DIIS Working Paper, consulting senior researcher Morten Broberg demonstrates this peculiarity and examines its likely causes. Moreover, Broberg argues that the extensive use of soft law measures affects the power balance between the different actors, in particular by strengthening the position of the Member States at the cost of, first of all, the Commission and the European Parliament.
Keywords: 330